Social impact ivesting in Germany: crrent ipediments from ivestors’ and scial etrepreneurs’ prspectives - Glänzel, Gunnar; Scheuerle, Thomas (Voluntas, 2016)
The paper provides empirical evidence on impediments of the emerging social impact investment field in Germany. The study is based on 19 in-depth interviews with social impact investing funds, investment advisors, and social entrepreneurs as investees. It takes an explorative approach because of the nascent stage of research on the subject. By systematically relating the perspectives of the actors involved, the study gives a broad empirical picture on the major challenges for social impact investing in Germany. Results reveal nine critical problem areas we have arranged along three dimensions: financial returns, social returns, and relationships and infrastructure. They comprise investors’ and social entrepreneurs’ practices, institutional settings which are still heavily influenced by peculiarities of the German welfare systems, as well as undeveloped framework conditions in the social investment market. By interpreting the results through a lens of conflicting institutional logics, we further contribute to this research stream by showcasing social impact investing as a core area of friction between the logics of the market and civil society.
Published online: 21 July 2015
Gesehen am 18.06.2020